Co-gasification and co-combustion of industrial solid waste mixtures and their implications on environmental emissions, as an alternative management. (1st January 2020) - Valdés, Carlos F.; Marrugo, Gloria P.; Chejne, Farid; Marin-Jaramillo, Alfredo; Franco-Ocampo, Jorge; Norena-Marin, Liliana
Highlights: Thermal co-processing for the final disposal of the waste reduced the mass in 45 wt.%. Syngas of 5.0 MJ/Nm 3 is a value-added alternative to sustainable management of waste. Co-pelletizing produced a homogeneous synergistic biofuel from heterogeneous waste. Abstract: The primary sludge produced by the wastewater treatment plant of a pulp and paper mill has high physicochemical heterogeneity, which limits the efficiency of thermochemical methodologies for the final disposal of this residue. As a solution, co-pelletization of the Primary Sludge (PS) with two other principal Industrial Solid Residues (ISRs) of the plant, Coal Boiler Ashes (CBA) and Wood Waste chips (WW), was proposed as a way to valorize the PS for energy use, while reducing dewatering costs. The energy potential was evaluated through a series of thermal co-processing tests of disaggregated and pelletized mixtures. Due to their differing fixed-carbon-to-volatile-material ratios, combining the ISRs resulted in a reduction of up to 45% of the mass of the ISR generated, improving the disposal conditions and achieving a minimum thermal power of 5.0 MJ/Nm 3 through gasification. Finally, the environmental implications of the thermal co-processing of the wastes were assessed, finding very low impacts due to pollutant emissions, in accordance with the legal environmental regulations in force in Colombia.